Understanding Community Water System Disinfection Practices in the United States. Issue 6 (2nd July 2021) - Gibson, Mark C.; Bartrand, Timothy A.
Key Takeaways: A novel analysis was conducted of utility‐provided and US Environmental Protection Agency–collected data on disinfection practices for small, medium, large, and very large community water systems. The analysis includes a total of 3, 823 systems across four size categories that collectively serve more than 217 million US customers. In the United States, chlorine‐based disinfectants are by far the most widely used for both centralized (primary) and residual (secondary) disinfection in the distribution system.